A RHETORICAL ANALYSIS OF COMMENTS AND DELIVERY STRATEGY ON TED TALKS - Ildi Kurniawan (JOALL (Journal of Applied Linguistics and Literature), 2021)
The purpose of this research is to describe the comments and its delivery strategy on the speech entitled “Do Schools Kill Creativity? by Sir Ken Robinson on TED.com. The data of this research were 50 comments of the videos (2016-2020) which contained comments on speaker or talk style not relating to talk content.  This research adopted the comment theory analysis by Tsou, A. et.al (2014). Coding process and content analysis was used to see delivery strategy by the speaker. The findings of the research showed that from the total of the comments, there were 38 comments on speaker delivery, then followed by comment on praise and criticism of speaker, 13 and 2 comments, respectively. There was no comment on both personal anecdote and other comments on the speaker. Also, from the comments on speaker delivery, it was revealed that the comments on the quality of delivery were attractive, sincere, knowledgeable, fluent, accurate, effective, and efficient. Finally, it was also found that both verbal and non-verbal delivery strategies were used very well by the speaker in his speech.